Using Picea/Pinus Ratios from the Wilcox Pass Core, Jasper National Park, Alberta, to Investigate Holocene Timberline Fluctuations - Beaudoin, Alwynne (Géographie physique et Quaternaire, 1986)
ABSTRACTHolocene timberline fluctuations are investigated using Picea/Pinus ratios from the tephra and radiocarbon-dated Wilcox Pass Core (52°14'N, 117°13'W). Timberline elevations are calibrated by comparing Picea/Pinus ratios from the core with modern ratios obtained in surface samples of a transect from alpine vegetation in Wilcox Pass into subalpine forest in adjacent Sunwapta Pass. Ratios higher than present ratios from the site imply higher-than-present timberline elevation. The Picea/Pinus ratios imply higher-than-present timberline between ca. 6540-1480 yr BP, with a minimum about 4210 yr BP, while timberline was lower than present between ca. 1480 - 540 yr BP and increased in elevation after 540 yr BP. This record substantially agrees with other palaeoenvironmental records from the region. The main limitation on the technique is that it can only be applied since similar-to-present vegetation became established in the area. Hence, Piceal Pinus ratios from the Wilcox Pass core prior to ca. 6540 yr BP cannot readily be interpreted by this method.